The beneficial role of curiosity on route memory in children - Sivashankar, Yadurshana; Fernandes, Myra; Oudeyer, Pierre-Yves; Sauzéon, Hélène (Frontiers in Cognition, 2024)
There has been a growing interest in the role of innate curiosity on facets of human cognition, such as in spatial learning and memory. Yet, it is unclear how state level curiosity evoked by the current environment could interact differentially with trait curiosity, to impact spatial memory performance. We assessed the influence of trait and state curiosity on route memory. Forty-two 10-year-old children with low and high-trait curiosity (20 Females; 22 Males) actively explored virtual environments that elicited varying levels of uncertainty (i.e., state-curiosity). As trait curiosity increased, so did memory performance in low and high uncertainty conditions, suggesting that high-curiosity children can better recruit cognitive resources within non-optimal environments. Children with high compared to low trait curiosity also reported greater feelings of presence during exploration. Importantly, in environments with medium uncertainty, children with low trait curiosity were able to perform as well as those with high curiosity. Results show that individual differences in trait curiosity influence route learning, and these interact dynamically with state-curiosity invoked within different environments.